2006
DOI: 10.3354/ame042027
|View full text |Cite
|
Sign up to set email alerts
|

Prokaryotic community structure and heterotrophic production in a river-influenced coastal arctic ecosystem

Abstract: Spatial patterns in prokaryotic biodiversity and production were assessed in the Mackenzie shelf region of the Beaufort Sea during open-water conditions. The sampling transect extended 350 km northwards, from upstream freshwater sites in the Mackenzie River to coastal and offshore sites, towards the edge of the perennial arctic ice pack. The analyses revealed strong gradients in community structure and prokaryotic cell concentrations, both of which correlated with salinity. Picocyanobacterial abundance was low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
105
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(126 citation statements)
references
References 70 publications
19
105
2
Order By: Relevance
“…Other data suggest that up to 84% of total prokaryotes are active in reducing 5-cyano-2, 3-ditoyl tetrazolium chloride in the western Arctic Ocean (Yager et al 2001, Huston & Deming 2002. These estimates are consistent with studies showing that a high fraction of bacteria (67 to 99%) and archaea (5 to 25%) are detected by fluorescence in situ hybridization (FISH) in Arctic water (Wells & Deming 2003, Garneau et al 2006, Wells et al 2006.…”
Section: Introductionsupporting
confidence: 78%
See 2 more Smart Citations
“…Other data suggest that up to 84% of total prokaryotes are active in reducing 5-cyano-2, 3-ditoyl tetrazolium chloride in the western Arctic Ocean (Yager et al 2001, Huston & Deming 2002. These estimates are consistent with studies showing that a high fraction of bacteria (67 to 99%) and archaea (5 to 25%) are detected by fluorescence in situ hybridization (FISH) in Arctic water (Wells & Deming 2003, Garneau et al 2006, Wells et al 2006.…”
Section: Introductionsupporting
confidence: 78%
“…Other data suggest that up to 84% of total prokaryotes are active in reducing 5-cyano-2, 3-ditoyl tetrazolium chloride in the western Arctic Ocean (Yager et al 2001, Huston & Deming 2002. These estimates are consistent with studies showing that a high fraction of bacteria (67 to 99%) and archaea (5 to 25%) are detected by fluorescence in situ hybridization (FISH) in Arctic water (Wells & Deming 2003, Garneau et al 2006, Wells et al 2006.Several bacterial groups are present in cold environments such as the Arctic Ocean. These groups include Bacteroidetes and several subdivisions of the Proteobacteria (Ferrari & Hollibaugh 1999, Bano & Hollibaugh 2002, Bowman et al 2003.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…Gammaproteobacteria is typically the predominant group in Arctic sea ice (Junge et al 2002;Brinkmeyer et al 2003;Bowman et al 2012) followed by Bacteroidetes (Deming 2010), whereas Alphaproteobacteria dominates in Arctic surface waters (Garneau et al 2006;Alonso-Sáez et al 2008). Accordingly, our results showed a dominance of Gammaproteobacteria and Bacteroidetes in the marine communities on the underside of landfast ice but no Alphaproteobacteria were detected (Fig.…”
Section: Microcosms To Study Hydrocarbon Degradationmentioning
confidence: 99%
“…This approach measures the production rate of proteins (Kirchman & Ducklow 1993) in both bacteria and archaea (Herndl et al 2005), although we assume a minor contribution of archaea in our samples, as observed on the Beaufort Sea shelf (< 1% to 7% of archaea in total DAPI counts; Garneau et al 2006) and in the Northwest Passage (2 to 13%; Wells & Deming 2003). Triplicate subsamples of 1.2 ml were spiked with 3 H-leucine (specific activity, 60 Ci mmol -1 ) to give a final concentration of 10 nM.…”
Section: Bacterial Productionmentioning
confidence: 99%